PEMBENTUKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN YANG TAAT ASAS HUKUM DAN PRINSIP-PRINSIP PERLINDUNGAN KONSUMEN - Parlindungan S, Gokma Toni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Indonesia already has a law that regulates consumer protection, namely Law No. 8 of 1999 concerning consumer protection. This law was passed by BJ Habibie, the transitional president at that time. In Article 4 of Law Number 8 of 1999 concerning Consumer Protection, it is stated that consumer rights include the right to comfort, security and safety in consuming goods or services. This law stipulates that every consumer, including Muslim consumers who constitute the majority of consumers in Indonesia, has the right to obtain goods and services that they are comfortable consuming. This law also states that consumers have the right to correct, clear and honest information regarding the condition and guarantee of goods or services. Keywords: Consumer Protection Law, Compliance with Principles, Principles.